2009
DOI: 10.18388/abp.2009_2467
|View full text |Cite
|
Sign up to set email alerts
|

Extradermal melanin transfer? Lack of macroscopic spleen melanization in old C57BL/6 mice with de-synchronized hair cycle.

Abstract: In quest of alternate, extradermal path of melanin transfer from skin to the visceral organs, we suggested that some portions of such melanin may be deposited in the spleen, which in young black C57BL/6 mice is often melanized. Here, we confirm these observation using young C57BL/6 female mice (up to 17 weeks) and show that this phenomenon cannot be observed in old animals where the hair cycle is not synchronized any more. The experiments were carried out both on spontaneous and depilation-induced hair cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, reduction of Cdk5 activity via an inhibitor (roscovitine) in HaCaT cells resulted in reduced adhesion of the cells to fibronectin, which was associated with reduced active states of β1 integrin 54 . In addition, the hair cycle determines skin thickness, which is highest during anagen VI and lowest during telogen in mice 39 , 55 . The results of the Western blot analysis showed that the expression level of transforming growth factor-βRII (TGF- βRII) was higher in the skin of the Cdk5 knockdown mice, whereas the expression of interleukin (IL) -1RI (IL-1RI) was lower in comparison with the wild-type mice (Supplementary Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduction of Cdk5 activity via an inhibitor (roscovitine) in HaCaT cells resulted in reduced adhesion of the cells to fibronectin, which was associated with reduced active states of β1 integrin 54 . In addition, the hair cycle determines skin thickness, which is highest during anagen VI and lowest during telogen in mice 39 , 55 . The results of the Western blot analysis showed that the expression level of transforming growth factor-βRII (TGF- βRII) was higher in the skin of the Cdk5 knockdown mice, whereas the expression of interleukin (IL) -1RI (IL-1RI) was lower in comparison with the wild-type mice (Supplementary Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in spleen pigmentation in mammals are observed by cyclophosphamide treatment, promoting a decrease in splenic melanization (MichalczykWetula et al, 2013). However, splenic melanin suffers gradual degradation during the mouse's life and this can be explained by synchronized skin melanization, parallel to the hair cycle progress (Michalczyk et al, 2009). This regulation can be explained by the transport of melanin through the leukocytes that increases visceral pigmentation deposition (Wassermann, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Histological findings of involuted hair follicles with atrophic skin imply an increased number of telogen hair follicles. Adult rodents still have a wave‐like hair growth pattern (12), although it is less synchronized than in young rodents (13), and only rapidly proliferating anagen follicles have been thought to be invaded by Se excess or deficiency (13–15). This can explain the focal alopecic patches rather than diffuse alopecia in the mice.…”
Section: Discussionmentioning
confidence: 99%